Clinical significance of fluid collection in the endometrial cavity in postmenopausal women - Bitner, Adam; Wlaźlak, Edyta; Surkont, Grzegorz; Suzin, Jacek; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Purpose: To assess the relationship between the presence of fluid in the endometrial cavity in postmenopausal asymptomatic women and endometrial pathology. Material and methods: Postmenopausal asymptomatic women with fluid in the endometrial cavity detected using TVS were included in the study. Results: At the beginning patients were divided into 3 groups. The first one was composed of 18 women in whom during TVS we detected fluid in the uterine cavity and narrow homogenous endometrium (width of one layer <3/2 mm). All pathological results demonstrated endometrial atrophy. The second group consisted of 5 patients with rugged trace of the endometrial cavity around fluid space. In 4 cases we found endometrial atrophy and submucous myomas. In 1 patient, where the rugged trace was not caused by myomas, there was endometrial carcinoma at a very early stage. 7 women (third group) had fluid and solid masses together. 4 of them had endometrial carcinoma, 2 – endometrial polyp and 1 – normal endometrium. Given no pathology in the first group, next patients with the same TVS picture were remained under observation. 21 women were under periodical TVS control during next 12 months. TVS pictures were unchanged. Conclusion: In the cases of detected fluid collection in the endometrial cavity during the TVS examination of postmenopausal asymptomatic women, uterus must be evaluated in all sections. Narrow (width of one layer <3/2 mm) homogenous endometrium seen around the fluid space manifests no endometrial pathology. In our opinion this result should be taken as a relative contraindication for invasive diagnostics because of higher risk of uterine perforation. In the case of rugged trace of the endometrial cavity around the fluid space invasive diagnostics should be considered. The detection of solid elements and septums is an indication for hysteroscopy and/or D&C.